Psychology Students and the Emergence of Impostor Syndrome - Fîșie, Diana-Madalina (New Trends in Psychology, 2025)
The study on the impostor syndrome among psychology students explores the impact of this phenomenon on young individuals pursuing a career in psychology. The impostor syndrome is characterized by a persistent feeling of insecurity and doubt about one’s abilities, even in the face of evident successes. In the context of psychology students, this research analyzes the factors that can contribute to the development and intensification of the impostor syndrome in this specific group. Academic pressures, social expectations, perceptions of perfection, and self-evaluation among psychology students are examined. Additionally, strategies for management and educational interventions are identified to help students overcome or reduce the impact of the impostor syndrome in their academic and professional journey in the field of psychology. This analysis contributes to a deeper understanding of the psychology students’ experience and provides guidance for the development of educational practices that promote self-esteem and confidence in their abilities.